решите понятно пожалуйста если получиться

3x^2=0

(x+1)(x-1)=0

4x^2-1=0

3x^2=5

4x^2-4x+1=0

x^2-16x-17=0

0,3x^2+5x=0

x^2-4x+5=0

разложить на множители x^2+x-6 2x^2-x-3

1

Ответы и объяснения

2013-03-05T16:51:01+04:00

3x^2=0   x=0

(x+1)(x-1)=0   x1=-1   x2=1

4x^2-1=0  x^2=1/4    x1=-1/2   x2=1/2

3x^2=5    x^2=5/3   x1=-V5/3    x2=V5/3

4x^2-4x+1=0    (2x-1)^2=0    2x-1=0    x=1/2

x^2-16x-17=0    x1=17   x2=-1

0,3x^2+5x=0     x(0.3x+5)=0    x1=0   x2=-5/0.3=-50/3

x^2-4x+5=0   D=16-20=-4<0   нет решений

 

x^2+x-6=(x+3)(x-2)

D=25   x1=(-1-5)/2=-3   x2=2

 

2x^2-x-3=2(x+1)(x-3/2)=(x+1)(2x-3)

 

D=1+24=25

x1=(1-5)/4=-1    x2=3/2